Diagnostic accuracy of Spanish and English screeners with Spanish and English criterion measures for bilingual students in Grades 1 and 2. (June 2022) - Baker, Doris Luft; Cummings, Kelli; Smolkowski, Keith
Abstract: The purpose of this study was to examine the diagnostic accuracy of English and Spanish language screeners when predicting reading comprehension outcomes in both languages at the end of Grade 1 and Grade 2. Participants were 1221 Latino/a bilingual students in Grade 1 and 1004 in Grade 2 who were attending bilingual programs in the Pacific Northwest and in Texas. We used ROC curve analyses to calculate the area under the curve (AUC; A ) for each measure. The decision thresholds we selected resulted in 71% of all comparisons having accuracy of at least 0.75. Letter naming, decoding, and oral reading fluency in Spanish were accurate in predicting reading risk on criterion measures in Spanish and in English in Grades 1 and 2 ( A value of 0.75 or above). English screeners, however, only predicted reading risk on the English criterion measure, but not on the Spanish criterion measure, with a few exceptions. Implications for practice and future research are discussed.